Cellular apoptosis and nitric oxide production in PBMC and spleen from dogs with visceral leishmaniasis - de Martini, Cleber Costa [UNESP]; de Andrade, Jéssica Thomé [UNESP]; de Almeida, Stéfani Karin Martiniano [UNESP]; Oliveira Silva, Kathlenn Liezbeth [UNESP]; de Rezende Eugenio, Flavia [UNESP]; dos Santos, Paulo Sergio Patto [UNESP]; de Lima, Valéria Marçal Felix [UNESP] (Elsevier, 2018)
Nitric oxide (NO) is involved in the death of the Leishmania parasite and regulation of apoptosis. We quantified the frequency of cells producing NO and its levels in the peripheral blood mononuclear cells (PBMC), leukocytes from spleen in Visceral Leishmaniasis (VL) symptomatic dogs and correlated NO levels with apoptosis and parasite load in the spleen. The percentage of NO+ cells and CD14+/NO+ was higher in PBMC and spleen cells in infected dogs than in controls. The levels of NO+ and CD14+/NO+ cells was higher in PBMC, but lower spleen of dogs infected than compared to control. Late apoptosis rates increased in PBMC and spleen of infected dogs compared to controls, and the NO levels and apoptosis not showed correlation. There was a positive correlation between the percentage of cells producing NO in the spleen and parasite load. The NO participates in the immune response in the canine VL, but it is not apoptosis inducer.
Keywords: Apoptosis; Canis familiaris; CD14; Cellular immunity; Flow cytometry; Macrophages; Nitric oxide; Parasite load; Visceral leishmaniasis; Zoonosis